Pengaruh Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) Terhadap Hasil Belajar IPA pada Tema 7 Indahnya Keberagaman di Negeriku Subtema 1 Keragaman Suku Bangsa dan Agama di Negeriku Kelas IV SD Negeri 101932 Perbaungan Tahun Pelajaran 2022/2023 - Lubis, Tasya Audina; Lubis, Rizka Hidayah Husin; Ramadhan, Nuri (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to analyze the influence of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on science learning outcomes for Theme 7, Subtheme 1 "Diversity of Ethnicities and Religions in My Country" in Grade IV of SD Negeri 101932 Perbaungan during the 2022/2023 academic year. The research is motivated by the low science learning outcomes due to insufficient student engagement and the over-reliance on monotonous teaching methods. A quantitative approach was applied using a quasi-experimental design. The sample consisted of 40 students selected through total sampling. Data analysis included validity and reliability tests, normality and homogeneity tests, as well as hypothesis testing through the t-test. The findings revealed that the average pretest score was 40, while the posttest average was 86.95. The t-test results indicated a significance value of sig < 0.05 (0.00 < 0.05), confirming a significant impact of the RADEC model on students' science learning outcomes. In conclusion, the RADEC learning model significantly enhances science learning outcomes, particularly in the study of ethnic and religious diversity in Grade IV at SD Negeri 101932 Perbaungan.